(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to shed light on the role of artificial intelligence in achieving Ambidexterity performance, as banks work to take advantage of modern technologies, artificial intelligence is an innovation that is expected to have a long-term impact, as well as banks can improve the quality of their services and analyze data to ensure that customers’ future needs are understood. . The Bank of Baghdad and the Middle East Bank were chosen as a community for the study because they had a role in the economic development of the country as well as their active role in the banking market. A sample of department managers was highlighted in collecting data and extracting results based on the checklist, which is the main tool for the study. An assumption was built that artificial intelligence contributes to building Ambidexterity performance ... as the study reached a set of results, namely the existence of different gaps for the dimensions of artificial intelligence, as the largest size was the space for the dimension (21%) of the Bank of Baghdad for the dimension of training and development. (21%), also that there is a high gap size for the Middle East bank due to the availability of expertise (17%). Also, after exploring opportunities, there was a high gap size for the Middle East bank.